Assessment of the impact of coaching on a company's performance: A review of methods - Angelina Roésa; Natalja Lace (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The aim of the present study is to provide an analysis of the literature about methods for assessing the impact of coaching on the performance of a company, and elaborate a framework of assessment methods emphasizing their use in the course of coaching interaction. The paper also explores the relationship between open innovation and coaching and proposes the themes for further research. The Scopus and Web of Science databases were selected for the review of the research papers in the business subject area. The review was guided by the following research questions: What methods are used for assessing the impact of coaching? How are these methods used in the course of the coaching interaction? How does coaching interrelate with open innovation? The findings suggest that the assessment of the impact of coaching on the individual's behavior and performance of a company is considered from different perspectives. The methods differ based on the needs for the assessment whether the process evaluation or the outcome evaluation is required. The analysis of the literature proves that the relationship between coaching and open innovation is mutually advantageous.
Keywords: 650; open innovation; coaching; company's performance; impact; methods for assessment